ESPECIFICAÇÕES E VERIFICAÇÃO GEOMÉTRICA EM UM AMBIENTE DE PLANEJAMENTO AVANÇADO DA QUALIDADE DO PRODUTO - Ribeiro, Luis F. M.; Eckhardt, Moacir; Sackser, Gilberto; Duarte, Luiz C. d. S.; Endruweit, Andreas A. B.; Schmidt, Audrien V. (Salão do Conhecimento, 2013)
Resumo